2019
DOI: 10.1101/624049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Significant enrichment of Herpesvirus interactors in GWAS data suggests causal inferences for the association between Epstein Barr virus and multiple sclerosis

Abstract: We exploited genetic information to assess the role of non-genetic factors in multifactorial diseases. To this aim we isolated candidate "interactomes" (i.e. groups of genes whose products are known to physically interact with environmental exposures and biological processes, plausibly relevant for disease pathogenesis) and analyzed nominal statistical evidence of association with genetic predisposition to multiple sclerosis (MS) and other inflammatory and non-inflammatory complex disorders. The interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…In this study, we obtained the transcriptomics datasets of these viruses and MS patients from the GEO database, and the correlation between EBV infection and MS risk was the most signi cant according to systematic analysis. The result was in line with previous studies, Rosella et al found that three herpesviruses showed statistical signi cance through the analysis between MS susceptibility genes and 20 interactomes, with EBV showing higher levels of signi cance compared to Human Herpesvirus 8 and, more evidently, to CMV [40]. Therefore, we dived deep into the roles of EBV in MS pathogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we obtained the transcriptomics datasets of these viruses and MS patients from the GEO database, and the correlation between EBV infection and MS risk was the most signi cant according to systematic analysis. The result was in line with previous studies, Rosella et al found that three herpesviruses showed statistical signi cance through the analysis between MS susceptibility genes and 20 interactomes, with EBV showing higher levels of signi cance compared to Human Herpesvirus 8 and, more evidently, to CMV [40]. Therefore, we dived deep into the roles of EBV in MS pathogenesis.…”
Section: Discussionsupporting
confidence: 91%